An Empirical Study of the Relationship between of Human Resource Management Practices and Job Performances among Employees in Small and Medium Enterprises in Selangor - Priya Darsihni Johnson; Eta Wahab (Research in Management of Technology and Business, 2023)
HRM practices are essential for SMEs in achieving various organizational objectives through improved employee job performance. The objective of this study was to determine the level of job performances among employees in Small and Medium Enterprise (SMEs), to determine the level of the HRM practices among employees in Small and Medium Enterprises (SMEs) and to identify the relationship between HRM practices and job performance among employees in Small and Medium Enterprises (SMEs). The problem is lack of employment practice in smaller businesses. Quantitative study was used in this study. This study used simple random sampling. An online survey was conducted among 320 employees with respondents rate of 83.33% in Selangor. The data was analyzed using both descriptive and Spearman’s correlation analysis. This research found that both HRM practices and job performances which at a high level. HRM practices were found to have a relationship with job performances.